2023
DOI: 10.1101/2023.06.15.545105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning and phylogenetic models identify predictors of genetic variation in Neotropical amphibians

Luis Amador,
Irvin Arroyo-Torres,
Lisa N. Barrow

Abstract: Many factors influence genetic variation within species, which is key for adaptation and survival in changing environments. Using amphibians as a study system, we investigated genetic diversity and structure within Neotropical species to provide insights into how natural history traits, phylogeny, and geographic characteristics influence intraspecific genetic variation. We assembled datasets for Neotropical amphibians using open-access databases for natural history traits, genetic sequences, phylogenetic trees… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Similarly, in amphibians, several recent studies have found within species genetic diversity to be lower in temperate regions in species with smaller ranges and at higher elevations (Barrow et al, 2020;Amador 2023). The methods used to detect these patterns are based on current taxonomic knowledge, and as such, rely on the assumption that the species designations used are accurate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in amphibians, several recent studies have found within species genetic diversity to be lower in temperate regions in species with smaller ranges and at higher elevations (Barrow et al, 2020;Amador 2023). The methods used to detect these patterns are based on current taxonomic knowledge, and as such, rely on the assumption that the species designations used are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the presence of variation in climate, rather than any species-specific trait or characteristic is the most identifiable driving force of within species genetic diversity for salamanders at this scale. Species traits were not a predictor of intraspecific genetic diversity in amphibians (Barrow et al, 2021;Amador et al, 2023) using a different measure of genetic variation within species (nucleotide diversity). Using similar methods, our results in salamanders differ from that found in mammals, where body size and range size were the most important predictors (Parsons et al, 2022).…”
Section: Significant Predictors Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation